2008
DOI: 10.2175/106143007x220743
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide Generation During Preservation of Chlorinated Wastewater Effluent Samples for Total Cyanide Analysis

Abstract: Dechlorinating agents and pH adjustment are often used to preserve wastewater samples for cyanide analysis. The effects of four approved preservation protocols on the results of the total cyanide analysis of effluents from four Water Reclamation Plants (WRPs) were examined. The results differed widely, and a clear pattern emerged. Immediate analysis without pH adjustment generally gave total cyanide concentrations below the reporting limit of 5 µg/L, irrespective of the dechlorinating agents used. When the pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Though more complex than drinking water, cyanide formation has been studied more extensively in domestic and industrial wastewater . Several wastewater studies have shown the cyanide can form during preservation and storage . Weinberg, et al , concluded that “an unknown, reactive, carbon-containing compound reacts with chlorine to form a cyanide precursor compound.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though more complex than drinking water, cyanide formation has been studied more extensively in domestic and industrial wastewater . Several wastewater studies have shown the cyanide can form during preservation and storage . Weinberg, et al , concluded that “an unknown, reactive, carbon-containing compound reacts with chlorine to form a cyanide precursor compound.…”
Section: Resultsmentioning
confidence: 99%
“…In an extensive study of hundreds of samples collected at four California wastewater treatment plants , , virtually all of the samples tested without pH preservation were nondetect for CN − at 5 µg/L, regardless of the dechlorinating agent used. But when these same samples were preserved by being adjusted to pH >12, cyanide tended to be detected.…”
Section: Resultsmentioning
confidence: 99%
“…This regulatory mantra is problematic for cyanide (Delaney & Blodget 2016a), and similar false positives from the sample preservation and testing have been demonstrated (Delaney et al 2007). Cyanide formation during wastewater preservation and testing has also been demonstrated (Stanley & Antonio 2012, Khoury et al 2008, Carr et al 1997, Delaney et al 1997). For wastewater, some treatment plants have been allowed by their regulators to avoid adding NaOH if they start the distillation immediately after sample collection, though USEPA stated that this is not allowed for drinking water (Wendleken 2016).…”
Section: Discussionmentioning
confidence: 98%
“…In 1994 an EPA consultant stated that the approved total cyanide methods in wastewater at that time were “dysfunctional” (Goldberg, 1994). Since then a number of researchers have examined the performance of various analytical methods for various forms of cyanide and the impact of sample preservation and pretreatments for positive and negative interferences (Milosavljevic, 1995; Carr, 1997; Weinberg and Cook, 2002; Zheng, 2003; Deeb, 2003; Gulino, 2004; Zheng, 2004a‐d; Zheng, 2004; Weinberg et al, 2005; Khoury et al, 2005; Pandit et al, 2006; Khoury et al, 2008; Stanley and Antonio, 2012). For example, Stanley and Antonio (2012) showed that preservation of wastewater samples with sodium hydroxide caused an “artificial increase” in cyanide levels compared to unpreserved samples and that this increase was not a matrix interference.…”
Section: Introductionmentioning
confidence: 99%